Interventions designed to limit gestational weight gain: a systematic review of theory and meta‐analysis of intervention components. Issue 6 (28th March 2013) - Hill, B.; Skouteris, H.; Fuller‐Tyszkiewicz, M.
Summary Limiting gestational weight gain (GWG) to recommended levels is important to optimize health outcomes for mother and baby. Surprisingly, a recent review revealed that theory‐based interventions to limit GWG were less effective than interventions that did not report a theory‐base; however, strict criteria were used to identify theory‐informed studies. We extended this review and others by systematically evaluating the theories of behaviour change informing GWG interventions using a generalized health psychology perspective, and meta‐analysing behaviour change techniques reported in the interventions. Interventions designed to limit GWG were searched for using health, nursing and psychology databases. Papers reporting an underpinning theory were identified and the CALO‐RE taxonomy was used to determine individual behaviour change techniques. Nineteen studies were identified for inclusion. Eight studies were informed by a behaviour change theory; six reported favourable effects on GWG. Overall, studies based on theory were as effective as non–theory‐based studies at limiting GWG. Furthermore, the provision of information, motivational interviewing, behavioural self‐monitoring and providing rewards contingent on successful behaviour appear to be key strategies when intervening in GWG. Combining these behaviour change techniques with dietary interventions may be most effective. Future research should focus on determining the exact combination of behaviour change techniques, or which underpinning theories, are most useful for limiting GWG.